REACTIVITY OF BLOOD LYMPHOCYTES IN PULMONARY TUBERCULOSIS - R. R. Khasanova; O. V. Voronkova; O. I. Urazova; V. V. Novitsky; A. K. Strelis; Yu. V. Stambula; A. E. Kolosova; V. A. Serebryakova; I. O. Naslednikova; O. V. Kolokolova; T. E. Budkina; N. P. Pirogova (Медицинская иммунология, 2014)
Evaluation of proliferative and IL-2-producing activity of peripheral blood lymphocytes wasperformed, using cultural methods, in patients with drug-sensitive and drug-resistant infiltrative pulmonary tuberculosis. The cell testing was performed at basal level and following in vitro stimulation with recombinant IL-2 and M. tuberculosis antigens. It was established that clinical course of infiltrative pulmonary tuberculosis, independently on drug sensitivity/resistance of the infectious pathogen, is accompanied by suppression of spontaneous lymphoproliferation. The levels of induced IL-2 production in drug-sensitive tuberculosis proved to be increased, whereas a reserve of IL-2-secreting reactivity of blood lymphocytes was lower than in drugresistant infection. Also, it was revealed that the level of lymphoproliferative response induced by IL-2, does not depend on clinical variant of tuberculosis, whereas stimulation of IL-2 production in blood lymphocytes is attained only in cases of drug-resistant tuberculosis variant.